IMPLEMENTASI MANAJEMEN SYARIAH DAN STRATEGI BISNIS DENGAN SYIRKAH MUDHARABAH DALAM MELAKUKAN EKSPANSI BISNIS PADA ISTANA LAUNDRY DI SAMARINDA - Mubarak, Muhammad Sirajul Amin; Tahir, Muhammad; Mahrus, Moh. (At-Tawazun, Jurnal Ekonomi Syariah, 2022)
The purpose of this research study is to determine the implementation of sharia management with syirkah mudharabah in conducting business expansion at the Laundry Palace in Samarinda and business strategies in expanding business at the Laundry Palace in Samarinda. The research method used is a type of field research (field research). Researchers used a triangulation approach in collecting data. Data collection techniques using interviews / interviews, field observations and documentation. The data analysis model in this study follows the concept given by Miles & Huberman. Miles & Huberman namely data reduction, data presentation, verification or data inference and conclusions. The results of this research are: 1) Implementation of sharia management with syirkah mudharabah in conducting business expansion at the Laundry Palace based on management functions, namely: a) Planning (planning), b) Organizing, c) Actuating, and d) Controlling (controlling). Meanwhile 2) Implementation of business strategies in conducting business expansion at Istana Laundry based on the basic elements of strategic management, namely: a) Environmental observation using SWOT analysis, b) Strategy formulation based on the results of SWOT analysis, c) Implementation of strategies carried out by Istana Laundry from the results of the formulation strategy and d) Evaluation.